Technological imagination to stay within planetary boundaries. Seven necessary transitions - Massimo Palme (Techne)
Technological imagination and innovation processes have always been at the basis of economic growth and the expansion of human domination over other species. Nevertheless, something seems to have got stuck. Can the leaps in technological development that make it possible to “reset” the clock to start growing again in a sustained form really be infinite? Or are we facing something different, a limit in the structural stability of the ecosystem itself? The worsening of the polycrisis – certainly also energetic – will require drastic solutions but should also finally allow the (re)emergence of radical ideas of renewal and transformation, as well as concrete proposals for spatial organisation associated with the new lifestyles they prefigure.